Chemical thinning of ’BRS Kampai’ peach trees - Farias, Roseli de Mello; Barreto, Caroline Farias; Zandoná, Renan Ricardo; Martins, Carlos Roberto; Mello-Farias, Paulo; Marodin, Gilmar Arduino Bettio (Pesquisa Agropecuaria Brasileira, 2019)
The objective of this work was to evaluate the effect of thinning with metamitron on the fruit yield and quality of ’BRS Kampai’ peach (Prunus persica) trees. The experiment was carried out in the municipality of Eldorado do Sul, in the state of Rio Grande do Sul, Brazil, in the 2016 and 2017 crop years. Treatments consisted of the application of 100, 200, 300, and 400 mg L-1 metamitron and of hand thinning 40 days after full bloom, besides control plants. Fruit abscission, effective fructification, number of fruits, and fruit yield per plant were evaluated. Regarding fruit quality, fresh fruit biomass, epidermis color, pulp firmness, soluble solids, total phenolic compounds, and antioxidant activity were assessed; fruits were also classified into diameter classes. For fruit abscission, the effect of the application of 100 mg L-1 metamitron is similar to that of hand thinning. Fruit yield and mean mass in all treatments with metamitron are similar to those obtained by hand thinning. The application of metamitron does not affect the fruit quality of peach trees. Chemical thinning with metamitron may be an alternative to hand thinning in peach trees used for the production of fruits for fresh consumption.